Anaphoric Processing of the Null Pronoun in Monolingual Speakers of Brazilian Portuguese: An Online Study - Rita; Holanda, Karla; Ferrari-Neto, José; Barbosa (East European Journal of Psycholinguistics, 2019)
The aim of this paper was to investigate anaphoric processing of the null pronoun in Brazilian Portuguese and determine whether the perception of morphological gender features has a disambiguating effect during the process of reading. This feature enables the anaphoric null pronoun to be interpreted as referring to either the subject or object. We assume the proposal put forth by Carminati (2005) regarding the resolution of the null subject pronoun, which is based on the investigation of the processing of full and null pronouns in Italian. The sample of the present study was composed of 32 speakers of university-level Brazilian Portuguese. The stimuli were temporal adverbial subordinate clauses with the manipulation of the gender feature in the participle as disambiguating information. The authors used the self-paced reading experimental paradigm with a control response. The results were in line with that predicted by the Feature Strength Hypothesis and Antecedent Position Hypothesis put forth by Carminati (2005).ReferencesAriel, M. (1991). The function of accessibility in a theory of grammar. Journal of Pragmatics, 16(5), 443-463. doi: 10.1016/0378-2166(91)90136-LCarminati, M. N. (2002). The processing of Italian subject pronouns. Dissertação de doutoramento, University of Massachusetts at Amherst, Amherst, MA: GLSA Publications.Carminati, M. N. (2005). Processing reﬂexes of the Feature Hierarchy (Person > Number > Gender) and implications for linguistic theory. Lingua, 115, 259–285. doi: 10.1016/j.lingua.2003.10.006Lasnik, H. & Lohndal, T. (2017). Noam Chomsky. In Oxford Research Encyclopedia of Linguistics. doi: 10.1093/acrefore/9780199384655.013.356Duarte, M. E. L. (2015) A perda do princípio “Evite Pronome” no Português Brasileiro. Campinas, SP: EDUNICAMP.Filiacia, F. Soracea, A., Carreiras M. (2013) Anaphoric biases of null and overt subjects in Italian and Spanish: a cross-linguistic comparison. Language, Cognition and Neuroscience, doi: 10.1080/01690965.2013.801502Gelormini-Lezama, C., Almor, A. (2011). Repeated names, overt pronouns, and null pronouns in Spanish, Language and Cognitive Processes, 26(3), 437-454. doi: 10.1080/01690965.2010.495234Gonçalves, A. V. G., Sousa, M. L. (2012). Ciências Da Linguagem: O Fazer Cientifico?. (1. Ed.). São Paulo, SP. Editora Mercado de letras.Grosjean, F. (1996). Living with Two Languages and Two Cultures. In I. Parasnis, Ed. Cultural and language diversity and the deaf experience. (pp. 20-37). Cambridge: Cambridge University Press.Kaiser, E., Fedele, E. (2019). Reference resolution: a psycholinguistic perspective. J. Gundel & B. Abbott, (Eds.). The Oxford Handbook of Reference. doi: 10.1093/oxfordhb/9780199687305.013.15Lapertua, M. (2004) Sujeito nulo na aquisição: um parâmetro em mudança – sujeito preenchido na aprendizagem: a eterna tentativa de mudança. Revista do Gelne, 6(1), 141.Limberger, B., Buchweitz, A. (2012). Estudos sobre a relação entre bilinguismo e cognição: o controle inibitório e a memória de trabalho. Letrônica, 5(3), 67-87,Lucchesi, D. (2009). A realização do sujeito pronominal. In D. Lucchesi, A. Baxter, & I. Ribeiro, (Eds.). O português afro-brasileiro (pp. 165-183). Salvador, BA: EDUFBA.Presuss, E. O., Finger, I. F. (2018). A dinâmica do Processamento Bilíngue. Campinas, SP. Pontes Editoras.Veríssimo, V. (2017). A evolução do conceito de parâmetro do sujeito nulo. Entrepalavras, Fortaleza, 7, 76-90.Xavier, G. R. (2006). Português Brasileiro como Segunda Língua: Um Estudo sobre o Sujeito Nulo. Campinas, SP: EDUNICAMP.